2013
DOI: 10.1111/ijcp.12065
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, long-term evaluation of the safety, efficacy and tolerability of avanafil in male patients with mild to severe erectile dysfunction

Abstract: The long-term tolerability and improvement in sexual function, coupled with rapid onset, suggest that avanafil is well suited for the on-demand treatment of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 16 publications
3
52
0
2
Order By: Relevance
“…Present data were confirmed by Belkoff et al [25] in a 52-week, open-label extension of two placebo-controlled RCTs [15,20] including 712 subjects with or without diabetes. All patients in this preplanned extension trial were initially assigned to treatment with avanafil 100 mg.…”
Section: Results Evaluationsupporting
confidence: 78%
See 2 more Smart Citations
“…Present data were confirmed by Belkoff et al [25] in a 52-week, open-label extension of two placebo-controlled RCTs [15,20] including 712 subjects with or without diabetes. All patients in this preplanned extension trial were initially assigned to treatment with avanafil 100 mg.…”
Section: Results Evaluationsupporting
confidence: 78%
“…Interestingly, only three subjects (0.4%) requested that their avanafil dose be decreased, confirming the good safety profile of this PDE5i. [25] Accordingly, the results provided by our meta-analysis showed that avanafil 100 and 200 mg were well tolerated and not associated with any increased risk of serious adverse events, in comparison with placebo. In addition, no risk of discontinuation of avanafil therapy due to drug-related adverse events was observed.…”
Section: Results Evaluationmentioning
confidence: 64%
See 1 more Smart Citation
“…There was no restriction with regard to the intake of the drug together with food or alcohol; patients who were on alpha-blocker medication were not excluded from the study. [Belkoff et al 2011]. There were no serious drug-related adverse events.…”
Section: Basic Research Findingsmentioning
confidence: 99%
“…228 There are three level 1 studies 20,24,229 and one open-label extension study (level 2) that have confirmed the sustained efficacy and safety of avanafil for 1 year. 230 The overall grade of recommendation is A.…”
Section: Avanafilmentioning
confidence: 99%